Ligand-free Pd catalyzed cross-coupling reactions in an aqueous hydrotropic medium - Jadhav, Sanjay N.; Kumbhar, Arjun S.; Rode, Chadrashekhar V.; Salunkhe, Rajashri S. (Green Chemistry, 2016)
A simple, efficient and ligand-free protocol for the Suzuki-Miyaura reaction and base-free Heck-Matsuda reactions under mild reaction conditions have been developed over palladium supported on activated carbon (Pd/C) in an aqueous hydrotropic solution. The catalyst Pd/C was fully characterized by TG-DTA, SEM, EDS, XRD, XPS, BET and ICP-AES analyses. This green methodology represents a cost-effective and operationally convenient method for the synthesis of a variety of biaryls, prochiral ketones, and acrylates under the conditions that are tolerant for a broad range of functional groups with good to excellent yields. The developed Pd/C-aqueous hydrotrope combined catalytic system is well suited for the 3R approach (reducible, robust, and recyclable) for different cross-coupling reactions without an appreciable loss of its activity.

Efficient palladium catalyzed Mizoroki-Heck cross-coupling in water - Jadhav, Sanjay N.; Rode, Chandrashekhar V. (Green Chemistry, 2017)
The homogeneous Pd-catalysed Mizoroki-Heck coupling reaction was successfully performed in water in the absence of any additives under aerobic conditions. The various key reaction parameters that affect the yield of the desired cross-coupling product were optimized. The Pd(PPh3)(4)/Et3N/H2O/98 degrees C catalyst system was found to be highly active (TOF = 12 to 14 h(-1)) towards achieving excellent yield of the Mizoroki-Heck coupling products for a wide range of electron-withdrawing as well as electron-donating aryl bromides and chlorides in the shortest reaction time. Pd(PPh3) 4 catalyst deactivation during the Mizoroki-Heck coupling reaction was investigated and to evolve a strategy for achieving ten times Pd-metal recyclability without appreciable loss of its activity. Thus, the proposed mechanism provides access to a variety of olefins in aqueous medium, making this protocol eco-friendly.

Bio-surfactant: a green and environmentally benign reaction medium for ligand-free Pd-catalyzed Mizoroki-Heck cross-coupling reaction in water - Patil, Seema P.; Jadhav, Sanjay N.; Rode, Chandrashekhar V.; Shejwal, Rajendra V.; Kumbhar, Arjun S. (Transition Metal Chemistry, 2020)
A simple and efficient protocol for the ligand-free Mizoroki-Heck coupling reaction of various aryl bromides with different olefins has been reported by using in situ generated PdNPs of size 5-10 nm in aqueous solution of bio-surfactant. The bio-surfactant used in this study is a saponin extract of the seeds of pericarps (pods) of theAcacia concinnaplant. The in situ generated PdNPs have been characterized by various techniques such as HRTEM, EDS and XPS. The influence of various parameters such as the nature and amount of bases, the nature of Pd precatalysts as well as the effect of temperature has been investigated on Mizoroki-Heck coupling reaction. The generated PdNPs significantly coupled the various aryl bromides with different olefins in aqueous extract of the seeds of pericarps (pods) of theAcacia concinnaplant at 100 degrees C. [GRAPHICS] .

Organocatalytic cascade knoevenagel-michael addition reactions: direct synthesis of polysubstituted 2-amino-4H-chromene derivatives - Jadhav, Sanjay N.; Patil, Seema P.; Sahoo, Dipti Prava; Rath, Dharitri; Parida, Kulamani; Rode, Chandrashekhar V. (Catalysis Letters, 2020)
In this report, we documented novel strategy for the synthesis of bioactive polysubstituted 2-amino-4H-chromine derivatives under a heterogeneous Al-MCM-41-LDH@APTES (ALAM) catalysis. A synthetic procedure is developed to prepare Al-MCM-41-LDH@APTES (ALAM) heterogeneous basic catalysts. Mesoporous Al-MCM-41 is functionalized by known grafting chemistry via layered double hydroxide (LDH) nanosheets and (3-aminopropyl)triethoxysilane (APTES) moiety as a basic organocatalyst. The resulting catalysts contain amino group functionality on the external surface as well as inside the layers and the basicity can be tuned by the loading of APTES. The samples were fully characterized by Si-29 and C-13 CP/MAS NMR, infrared absorption spectroscopy, TEM, XPS, EDX, TGA, XRD, CO2-TPD, N-2 adsorption isotherms measurements, and they were successfully examined for the cascade type Knoevenagel-Michael addition reactions. The product yields associated with these substrates were optimized, and key reaction parameters affecting the yields were identified. The present catalytic method is simple and robust for diversity oriented synthesis which proceeds good to excellent yields without generating any hazards waste. The broad substrate scope, excellent functional group compatibility makes this protocol highly useful towards synthesis of polysubstituted alpha-cyanoacrylates, alpha-cyanoacrylonitriles and 2-amino-4H-chromenes with an electron-donating or electron-withdrawing group. We have also successfully established a flow reaction system, gram-scale synthesis as well as catalyst recyclability up to six catalytic cycles without appreciable loss of its activity. Graphic
Keywords: 2-Amino-4H-chromines; Amine functionalized solid catalysts; cascade synthesis; Diversity oriented syntheses (DOS); flow chemistry

ZrO2 supported Cu nanoparticles for sonogashira and ullmann coupling reactions under palladium-free conditions - Patil, Seema P.; Rajmane, Archana S.; Jadhav, Sanjay N.; Rajmane, Vijaya S.; Rode, Chandrashekhar V.; Kumbhar, Arjun S. (Catalysis Letters, 2024)
Cu nanoparticles supported on ZrO2 (CuNPs@ZrO2) were synthesized using a one-step co-precipitation process, and their application in C-C coupling reactions was investigated. The catalyst was characterized using XRD, XPS, SEM, TEM, and TGA techniques. The prepared catalyst was used for the Sonogashira cross-coupling reactions of aryl bromides with phenyl-acetylene in the presence of K2CO3 in DMF at 110 degrees C, which resulted in substituted alkynes with good to excellent yields. The protocol was also extended for the Ullmann coupling reactions of aryl iodides under similar reaction conditions, yielding the desired products with good to excellent yields without homo-coupling. Interestingly, unlike other copper catalysts, the present catalyst worked under air and did not require an inert atmosphere to prevent alkyne. This catalytic system is versatile, tolerant, and significantly cheaper than the ``traditional'' Pd-catalyzed Sonogashira cross-coupling of terminal alkynes with aryl halides. The catalyst could be reused for five catalytic cycles with no significant change in the product yield. All of these characteristics make our prepared CuNPs@ZrO2 catalyst quite suitable for the gram-scale synthesis of biaryls and alkynes, with a simple workup.{GRAPHIACAL ABSTRACT
Keywords: CuNPs; Recyclability; Sonogashira coupling; Ullmann coupling; ZrO2